2000
DOI: 10.1056/nejm200012073432304
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Sarcomere Protein Genes as a Cause of Dilated Cardiomyopathy

Abstract: Mutations in sarcomere protein genes account for approximately 10 percent of cases of familial dilated cardiomyopathy and are particularly prevalent in families with early-onset ventricular dilatation and dysfunction. Because distinct mutations in sarcomere proteins cause either dilated or hypertrophic cardiomyopathy, the effects of mutant sarcomere proteins on muscle mechanics must trigger two different series of events that remodel the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
288
0
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 638 publications
(299 citation statements)
references
References 34 publications
5
288
0
6
Order By: Relevance
“…The onset of disease was more pronounced in MHC F764L/ϩ mice than in MHC S532P/ϩ mice. These findings are consistent with the clinical features of most patients with the S532P mutation, who show slow disease progression and live into their 70s; patients carrying the F764L mutation display evidence of disease during childhood, which progresses slowly during adulthood (6).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The onset of disease was more pronounced in MHC F764L/ϩ mice than in MHC S532P/ϩ mice. These findings are consistent with the clinical features of most patients with the S532P mutation, who show slow disease progression and live into their 70s; patients carrying the F764L mutation display evidence of disease during childhood, which progresses slowly during adulthood (6).…”
Section: Resultssupporting
confidence: 83%
“…Dilated hearts are hypocontractile, with systolic dysfunction leading to a reduced ejection fraction: a hallmark of a failing heart (2, 3). Only recently have autosomal dominant missense mutations to the ␤-cardiac myosin heavy chain (MHC) been identified that result in DCM (5,6). Because the primary defect resides within the heart's molecular motor, we hypothesized that altered cardiac contractile function in DCM hearts might reflect changes in the mutant myosin's ability to generate force and motion as it cyclically interacts with actin during its hydrolysis of ATP.…”
mentioning
confidence: 99%
“…There is a high incidence of sudden cardiac death in infants as well as adults among patients harboring the TnT-⌬K210 mutation (8). The decreased ATPase activity and Ca 2ϩ sensitivity as well as impaired force production that we observe could provide the inciting stimulus for the sarcomere to remodel leading to DCM.…”
Section: Discussionmentioning
confidence: 65%
“…None of the individuals affected with DCM exhibited ventricular hypertrophy, a hallmark feature of hypertrophic cardiomyopathy. Medical records of deceased individuals from these families revealed sudden deaths of two infants with infantile cardiomyopathy and three young adults (8). Li et al (9) reported another novel TnT mutation, TnT-R141W, in the Tmbinding site of TnT in a large family of 72 members.…”
mentioning
confidence: 99%
“…Despite decades of research, heart failure remains a major cause of death and mortality32333435363738. Therefore, improved understanding of the molecular mechanisms underlying heart failure is still urgently needed to develop novel targeted treatment strategies.…”
Section: Discussionmentioning
confidence: 99%